Visual Attention, Bias, and Social Dispositions Toward People With Facial Anomalies: A Prospective Study With Eye-Tracking Technology - Villavisanis, Dillan F; Workman, Clifford I; Zapatero, Zachary D; Vu, Giap H; Humphries, Stacey A; Blum, Jessica D; Cho, Daniel Y; Swanson, Jordan W; Bartlett, Scott P; Chatterjee, Anjan; Taylor, Jesse A (Annals of plastic surgery, 2023)
Facial attractiveness influences our perceptions of others, with beautiful faces reaping societal rewards and anomalous faces encountering penalties. The purpose of this study was to determine associations of visual attention with bias and social dispositions toward people with facial anomalies. Sixty subjects completed tests evaluating implicit bias, explicit bias, and social dispositions before viewing publicly available images of preoperative and postoperative patients with hemifacial microsomia. Eye-tracking was used to register visual fixations. Participants with higher implicit bias scores fixated significantly less on the cheek and ear region preoperatively (P = 0.004). Participants with higher scores in empathic concern and perspective taking fixated more on the forehead and orbit preoperatively (P = 0.045) and nose and lips (P = 0.027) preoperativel. Participants with higher levels of implicit bias spent less visual attention on anomalous facial anatomy, whereas participants with higher levels of empathic concern and perspective taking spent more visual attention on normal facial anatomy. Levels of bias and social dispositions such as empathy may predict layperson gaze patterns toward those with facial anomalies and provide insights to neural mechanisms underlying the "anomalous is bad" paradigm.